2021
DOI: 10.1093/g3journal/jkab369
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution in situ analysis of Cas9 germline transcript distributions in gene-drive Anopheles mosquitoes

Abstract: Gene drives are programmable genetic elements that can spread beneficial traits into wild populations to aid in vector-borne pathogen control. Two different drives have been developed for population modification of mosquito vectors. The Reckh drive (vasa-Cas9) in Anopheles stephensi displays efficient allelic conversion through males but generates frequent drive-resistant mutant alleles when passed through females. In contrast, the AgNos-Cd1 drive (nos-Cas9) in An. gambiae achieves almost complete allelic conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…This then could explain the observed activity of gene drive for male parentals in the AegNosC109 GD line and the absence of a maternal effect. Further, Terradas et al (2021) showed that in An. stephensi, while β2-tubulin transcripts were male-specific, they were also expressed in the late stages of spermatogenesis, which would preclude the use of the β2-tubulin for the purposes of a CRISPR/Cas9 based gene drive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This then could explain the observed activity of gene drive for male parentals in the AegNosC109 GD line and the absence of a maternal effect. Further, Terradas et al (2021) showed that in An. stephensi, while β2-tubulin transcripts were male-specific, they were also expressed in the late stages of spermatogenesis, which would preclude the use of the β2-tubulin for the purposes of a CRISPR/Cas9 based gene drive.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Cas9 is under control of the maternal nanos gene promoter, it would be expected that Cas9 mRNA would be provided maternally. An elegant study by Terradas et al (2021) demonstrated that the nanos-driven Cas9 transcripts from the AgNosCd1 GD line (Carballar-Lejarazú et al, 2020) were indeed expressed in the nurse cells along with native nanos transcripts; however, unlike the native nanos transcripts, the Cas9 transcripts were found only at very low levels or were absent in the egg. By contrast, in males, Cas9 expression driven by the nanos regulatory elements paralleled that of the native nanos transcript.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While efforts have been made to experimentally validate the intended transgene expression pattern ( Hammond et al, 2016 ; Kandul et al, 2020 ; Terradas et al, 2021c ; Weitzel et al, 2021 ), there are fewer cases where this has been done throughout development ( Li et al, 2017 ). The result of this is that any hypothesis about the ideal expression/activity pattern for HEGs is currently essentially unfalsifiable as any exception to a proposed hypothesis can easily be explained away by the many ways a drive may fail to recapitulate the intended expression pattern, at the needed expression level.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent hypothesis is that interchromosomal HDR after a DNA break is most likely if the DNA break coincides with meiosis I ( Burt and Trivers, 2006 ; Xu et al, 2017 ; Champer et al, 2018 , Champer et al, 2020 S. E. ; Grunwald et al, 2019 ; Pfitzner et al, 2020 ; Terradas et al, 2021b ; Terradas et al, 2021c ; Kandul et al, 2021 ; Li et al, 2021 ; Taxiarchi et al, 2021 ; Weitzel et al, 2021 ; Xu et al, 2021 ). During this time chromosomal homologs exchange information through crossing-over events.…”
Section: The Main Technical Challenges Facing Synthetic Hegsmentioning
confidence: 99%